Supporting Millennials in Achieving Work-Life-Balance : Identifying the work-life-balance tools and unique characteristics of Millennials - Kokkarinen, Eeva (My University, 2022)
This study discusses the importance of millennials and their work-life balance. The purpose of this study is to identify how millennials are supported in achieving work-life balance in their life with three sub-objectives: Are managers aware of the generational differences when it comes to work values, What work-life balance tools are available, and What tools are attractive to millennials. The theoretical background of the study consists of literature relating to the concepts of work-life balance and the different work-life balance tools, possible barriers to work-life balance, and lastly millennials and their work expectations. This study was performed as a qualitative research approach and the empirical research conducted for this study is based on semi-structured interviews. In total 5 interviews were conducted, three of them via email and two of them via Skype. The findings of this research emphasize the importance of the management in recognizing millennial employees, their unique characteristics, and the best practices in managing them. The findings of this study enhance our understanding of what millennials look for and what is important for them in terms of work-life balance.
Keywords: Work-Life balance, Millennials, Qualitative research, Flexible working solutions